Teachers in the 21st Century: Emotional Intelligence Skills Make the Difference - Valente, Sabina (2022)
Teaching is intrinsically an emotional practice, given the centrality of emotions in the teaching and learning process. That way, teachers in the 21st century increasingly have to have skills for responding to classroom emotional situations. Therefore, the way teachers shape and handle their emotional states and those of their learners is central to educational success. Focused on studies carried out that suggest teachers’ emotional intelligence like a success indicator for a healthy pedagogical relationship, this chapter makes a reflective approach to the meaning of teachers’ emotional intelligence skills in their professional activity (e.g., professional well-being, teacher-student relationship, and student academic achievement). Consequently, it will be necessary to integrate emotional skills in the pre-service teachers’ curriculum as skills needed for teaching practice and also to build capacity and support students during challenging times that constantly changing.